Chemical Compositions, In-vitro Antioxidant, Anti-microbial, Anti-inflammatory and Cytotoxic Activities of Essential Oil of Acorus calamus L. Rhizome from North-East India. Issue 5 (3rd September 2019) - Loying, Rikraj; Gogoi, Roktim; Sarma, Neelav; Borah, Angana; Munda, Sunita; Pandey, Sudin Kumar; Lal, Mohan
Abstract: Acorus calamus L. is an important aromatic medicinal plant, which has many biological activities. The aim of this study was to evaluate the potential in-vitro antioxidant, anti-microbial, anti-inflammatory and cytotoxic activities of rhizome essential oil of A. calamus . Hydro-distillation process was used to extract the essential oil from dry rhizome using Clevenger apparatus. The chemical compounds identified through GC/MS analysis revealed that β-asarone (82.42 %) as a major compound and calarene (2.41 %), euasarone (1.92 %), 2- methoxy-3-allylphenol (1.91 %) were minor compounds. The antioxidant activity of rhizome essential oil showed good free radical scavenging activity in DPPH assay (IC50 =1.68 μg/mL) as compared to standard, ascorbic acid (IC50 =1.48 μg/mL). Anti-microbial activity of rhizome essential oil showed the highest zone of inhibition against A. fumigates (16 mm) and lowest against S. cerevisiae (12 mm) at 500 μg/mL concentration among the tested fungal strains whereas, for bacterial strains, the highest zone of inhibition was shown against B. subtilis (12 mm) and lowest against B. cereus (8 mm) at the same concentration. Anti-inflammatory assay showed the IC50 value was 172.41 μg/mL whereas in the standard, sodium diclofenac, was 21.0 μg/mL. The toxicity study in A. cepa roots showed that there was negligible effect on the mitotic index (MI=4.20 %) by the rhizome essential oil; as compared to the positive control, EMS (MI=14.79 %) at 1 μL/mL. Based on these findings, it can be concluded that essential oil of A. calamus rhizome could serve as a natural antioxidant and anti-microbial source for commercial use.